Pengembangan Manajemen Sumber Daya Manusia Berbasis Total Quality Manajemen di Madrasah Aliyah Nurul Ummah Kotagede Yogyakarta - Radit Hijrawan (STAI Terpadu Yogyakarta, 2019)
Human resources (HR) become the dominant factor in an institution, including the education sector. Education requires quality human resources, to carry out its role in meeting the educational needs of the community. Also related to Madrasah Aliyah Nurul Ummah Kotagede Yogyakarta is one of the pesantren-based educational institutions which is expected to have a Total Quality Management system in the management of education. This shows educational institutions contribute to customer satisfaction, both internal and external customers. In this paper discusses the basic concepts of human resource management based on Total Quality Management in Madrasah Aliyah Nurul Ummah Kotagede Yogyakarta, which talks about the procedures for implementing human resource development, so that it gets results from the processes that have been carried out in the development of human resources in Madrasah Aliyah Nurul Ummah Kotagede Yogyakarta. Data collection while in the field is done by observation, interviews, and documentation, which can then be classified as qualitative research. Based on the research process, it can provide input and evaluation to make improvements in the development of Madrasah Aliyah Nurul Ummah Kotagede Yogyakarta for the future that is better than ever before.